Research Progress of Bionic Adaptive Camouflage Materials - Qiao, Yu; Meng, Zihui; Wang, Piaopiao; Yan, Dan (Frontiers in Materials, 2021)
Bionic adaptive camouflage material is a new artificial functional material, whose surface color can change adaptively according to the optical environments. Therefore, how to reduce the visual detectability of this material becomes a research hotspot of digital camouflage stealth technology. In order to clarify the limitations and opportunities of the bionic adaptive camouflage materials in the field of visual stealth, we summarize the applications of current adaptive camouflage materials and carry out a prospect of next-generation photonic crystal infrared camouflage material in this review. It is expected to provide a solution for the demand of digital camouflage adaptive materials in the modern battle field.